Identifying COVID-19 Infections From a Vaccinated Population Using Specific IgA Antibody Test - Cheng, Zhangkai J.; Zheng, Peiyan; Xue, Mingshan; Chen, Youpeng; Sun, Baoqing (Frontiers in Immunology, 2022)
We analyzed the serum from COVID-19 patients and vaccinated subjects, and found that the specific IgA titer level could be used to assist COVID-19 diagnosis, with an ROC of 0.862.